Pervasive Refusal Syndrome in Autistic Spectrum Disorder - Emily Claire Bond; Rosalind Yvonne Kirton Oliphant (Case Reports in Psychiatry)
Pervasive Refusal Syndrome (PRS) is a rare child psychiatric condition. We describe a case of PRS in a 9-year-old boy with a diagnosis of Autism Spectrum Disorder (ASD) presenting with severe weight loss due to extreme restriction of food and fluids. Other prominent symptoms included total mutism, school refusal, and self-neglect. He was admitted to a specialist Child and Adolescent Mental Health Unit. We discuss the symptoms present in this case and the differential diagnosis of ASD in PRS. Although this differential has briefly been considered one in previous case, there have been no reported cases of PRS with a prior diagnosis of ASD. We explore comorbidity and interaction of the two diagnoses. We discuss the possible impact of ASD as a predisposing factor upon the progression and prognosis of PRS.